PREVALENT NURSING DIAGNOSIS IN PATIENTS HOSPITALIZED WITH SEPSIS AT THE INTENSIVE CARE UNIT - Cintia Suemy Kagiyama Dutra; Laura Menezes Silveira; Aive Oliva Santos; Raíssa Pereira; Angelita Maria Stabile (Universidade Federal do Paraná, 2014)
The objective in this study was to identify the prevalent nursing diagnoses in patients hospitalized with sepsis, severe sepsis or septic shock at an Intensive Care Unit. The population consisted of patients over 18 years of age, hospitalized at the Intensive Care Unit between January and December 2010. The information was collected from the patient histories, according to the sociodemographic and clinical characteristics and nursing diagnoses registered. In the study period, 103 patients were hospitalized, 79.4% of whom died. The following nursing diagnoses were identified: risk for infection, risk for aspiration, risk for impaired skin integrity, impaired spontaneous ventilation, impaired gas exchange, ineffective cardiopulmonary tissue perfusion and impaired skin integrity. In conclusion, the identification of the diagnoses present in the histories of sepsis patients is expected to contribute to nursing care for these clients.